EKSPERIMENTASI MODEL PEMBELAJARAN THINK-TALK-WRITE DENGAN MIND MAPPING PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI DI KABUPATEN KUDUS TAHUN PELAJARAN 2015/2016 - Malikhah, Siti; Kusmayadi, Tri Atmojo; Sujadi, Imam (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of the research was to determine the effect of learning models on learning achievement viewed from student learning creativity. The learning models compared were Think-Talk-Write with Mind Mapping (TTW-MM), Think-Talk-Write (TTW) and direct instruction model. The research used the quasi-experimental research method. The population of the research was all of the students in grade VIII of junior high schools in Kudus regency on academic year 2015/2016. The size of the sample was 275 students consisted of 91 students in the first experimental group, 92 students in the second experimental group, and 92 students in the third experimental group. The results of the research are as follows. (1) The students instructed with the learning model TTW-MM had learning achievement as good as those instructed with the learning model TTW, and a both of them better than direct instruction, the students instructed with the learning model TTW had learningÂ achievement better than those instructed with direct instruction. (2) The students with the high creativity had learning achievement better than those with the medium creativity and low creativity, the students with the medium creativity had learning achievement better than those with the low creativity. (3) In each learning model, the students with the high creativity had learning achievement better than those with the medium creativity and low creativity, the students with the medium creativity had learning achievement better than those with the low creativity. (4) In each learning style, the students instructed with the learning model TTW-MM had learning achievement better than instructed with the learning model TTW and direct instruction, the students instructed with the learning model TTW had learningÂ achievement better than those instructed with direct instruction.Keywords : Think-Talk-Write with Mind Mapping, Think-Talk-Write, direct instruction, creativity learningÂ